2013
DOI: 10.1128/jcm.03142-12
|View full text |Cite
|
Sign up to set email alerts
|

Easily Modified Factors Contribute to Delays in Diagnosis of Clostridium difficile Infection: a Cohort Study and Intervention

Abstract: cAlthough rapid laboratory tests are available for diagnosis of Clostridium difficile infection (CDI), delays in completion of CDI testing are common in clinical practice. We conducted a cohort study of 242 inpatients tested for CDI to determine the timing of different steps involved in diagnostic testing and to identify modifiable factors contributing to delays in diagnosis. The average time from test order to test result was 1.8 days (range, 0.2 to 10.6), with time from order to stool collection accounting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…A rapid, accurate diagnosis followed by prompt treatment are critical in the management of CDI and prevention of transmission [38,39]. Barbut et al found that a change from toxigenic culture and CTA to a NAAT or a 2-step algorithm including GDH and NAAT resulted in a significant reduction in the time to reporting of test results and earlier initiation of treatment, reduced empiric therapy in patients without CDI, and a decrease in processing of multiple samples.…”
Section: Discussionmentioning
confidence: 99%
“…A rapid, accurate diagnosis followed by prompt treatment are critical in the management of CDI and prevention of transmission [38,39]. Barbut et al found that a change from toxigenic culture and CTA to a NAAT or a 2-step algorithm including GDH and NAAT resulted in a significant reduction in the time to reporting of test results and earlier initiation of treatment, reduced empiric therapy in patients without CDI, and a decrease in processing of multiple samples.…”
Section: Discussionmentioning
confidence: 99%
“…The average time taken to test for CDI in one study was 1.8 days [ 3 ], although other centers performing testing three times per day report turnaround times of 8 h [ 4 ]. The authors have previously reported a median turnaround time of 17.3 h in their institution’s laboratory [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the absence of toxin testing, our findings suggest that there is a need for efforts to reduce testing of patients not meeting clinical criteria for CDI testing. 3,9 In particular, reducing testing of patients with diarrhea but with no recent antibiotic exposure might be of benefit given our finding that patients with no recent antibiotic exposure were unlikely to shed spores. Finally, spores on skin and in the environment have been shown to be an important source for acquisition on hands of healthcare personnel 5,6,10 and therefore are likely to be an important source for transmission.…”
Section: Discussionmentioning
confidence: 90%
“…1 In practice, however, CDI tests are often ordered for patients without clinically significant diarrhea or with clear alternative explanations for diarrhea. 2,3 For example, Dubberke et al 2 reported that 36% of patients with orders for CDI testing did not meet criteria for diarrhea and 19% had received laxatives in the 2 days prior to stool collection. Such testing of patients not meeting clinical criteria for CDI testing may result in false-positive diagnoses of CDI due to detection of asymptomatic carriers of toxigenic C. difficile, particularly if sensitive nucleic acid amplification tests are used.…”
mentioning
confidence: 98%